Catching-up and falling behind: knowledge spillover from American to German machine tool makers - Ralf Richter; Jochen Streb (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2009)
In our days, German machine tool makers accuse their Chinese competitors of violating patent rights and illegally imitating German technology. A century ago, however, German machine tool makers used exactly the same methods to imitate American technology. To understand the dynamics of this catching-up process we use patent statistics to analyze firms' activities between 1877 and 1932. We show that German machine tool makers successfully deployed imitating and counterfeiting activities in the late 19th century and the 1920s to catchup to their American competitors. The German administration supported this strategy by stipulating a patent law that discriminated against foreign patent holders and probably also by delaying the granting of patents to foreign applicants. Parallel to the growing international competitiveness of German firms, however, the willingness to guarantee intellectual property rights of foreigners was also increasing because German firms had now to fear retaliatory measures in their own export markets when violating foreign property rights within Germany.
urn:nbn:de:bsz:100-opus-4037
Keywords: 330; Maschinenbau; Patent; Wissenstransfer; Spillover-Effekt; Patentrecht; Geschichte; Deutschland (bis 1945); USA